The Prospects for Poland Joining the Euro Area in the Context of the Theory of Optimal Currency Areas and Convergence Criteria - Pukin-Sowul, Paulina (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2021)
Objective: The aim of the study is to determine the benefits and threats of introducing the euro in Poland in the context of the theory of optimal currency areas and convergence criteria.Research Design & Methods: A critical analysis of the literature on the subject, both Polish and foreign, as well as statistical analysis based on data from the World Bank, The European Commission, the Polish Central Statistical Office, the Eurostat and TradingEconomics.com were used.Findings: Currently, the euro area does not meet the theory OCA assumptions, and Poland does not meet the convergence criteria. Therefore, Poland cannot join the euro area. Moreover, joining the European Monetary Union may open the door to more threats than benefits.Implications / Recommendations: Poland, as a country with a derogation, is obliged to meet the convergence criteria and join the euro area, but it is not ready at present. However, Poland and the euro area together could eventually create an optimal currency area.Contribution: The results contribute to the debate on European monetary integration and the prospects for the introduction of the euro in Poland and may constitute a basis for further research.